Epidemiological Profile of Snake Bites over 1-Year Period from Tertiary Care Centre in Maval Region of Maharashtra, India: Original Research Article - Rajesh Kharat1, Rahul Kedare2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Estimated deaths rate due to snake bites are more than 46,000 annually in our country. Ninety-seven to ninety eight percent bites occur in rural or remote areas. Snake bite is a one of common problem faced in rural India. It takes a high toll of lives mainly of working male of the family. The current prospective observational study was carried out to study the clinical and management by systematic approach of snake bites. The 245 cases of snake bite were hospitalized to Rural Hospital in a period of July 2017 to June 2018.The present data showed that majority (91.43%) of cases were encountered from rural area,in the age group ranging from 21 to 30years (24.90%) Majority were male patients (62.04%). Most affected were the agricultural laborers and farmers (56.33%). 60.82% of the cases were presented with bite over lower extremities .Most of the snake bite (75.97%) occurred during day time. July to October was the period in which most snake bite cases were observed. It was seen that syndromic or systematic approach was more effective in early diagnosis and treatment of snake bite. The average requirement of anti- serum venom (ASV) required for cobra bite was 16,krait bite 22,Russell’s viper bite 12 and saw scaled viper bite 10. The total duration of treatment in hospital for cobra bite were 6, krait bite 8, Russell’s viper bite 4 and saw scaled viper 4 days.